Phosphotungstic acid embedded sulfonated poly(arylene ether ketone sulfone) copolymers with amino groups for proton exchange membranes. Issue 101 (1st October 2015) - Xu, Lishuang; Han, Hailan; Liu, Meiyu; Xu, Jingmei; Ni, Hongzhe; Zhang, Hailong; Xu, Da; Wang, Zhe
Abstract : The acid–base interaction between HPW and the amino groups can immobilize HPW to maintain high proton conductivity at medium-high temperature in the composite membranes. Abstract : Sulfonated poly(arylene ether ketone sulfone) containing pendant amino groups (Am-SPAEKS)/phosphotungstic acid (HPW) composite membranes with different HPW content were prepared by the solution blend method as proton exchange membranes (PEM) for proton exchange membrane fuel cells (PEMFCs) that operate at medium–high temperatures. Am-SPAEKS was synthesized successfully by adjusting the molar feed ratio, which was confirmed by Fourier transform infrared (FT-IR) and 1 H NMR spectroscopy. FT-IR spectroscopy showed that there were acid–base interactions between the amino groups and HPW, as well as between HPW and the sulfonic groups. These interactions could stabilize HPW in the composite membranes, which was confirmed by SEM images. The water uptake and thermal stability of the composite membranes were improved compared with the Am-SPAEKS membranes. The water retention capacity and the mechanical property of the composite membranes also met the requirement for proton exchange membranes. The proton conductivity of the Am-SPAEKS/HPW30% composite membrane was as high as 0.091 S cm −1 at 120 °C. These results indicate that the Am-SPAEKS/HPW composite membranes have potential to be used as alternative proton exchange membrane materials for proton exchange membrane fuel cells at medium–high temperature conditions.